The impact of portfolio disclosure on hedge fund performance - Shi, Zhen (Journal of Financial Economics, 2017)
Consistent with the argument that portfolio disclosure reveals trade secrets, a difference-in-differences estimation suggests a drop in fund performance after a hedge fund begins filing Form 13F as well as an increase in return correlations with other funds in the same investment style. The drop in performance is concentrated among funds with larger expected proprietary costs of disclosure, for instance, funds that disclose a greater fraction of their assets or hold more illiquid stocks. The drop in performance cannot be fully explained by alternative explanations such as decreasing returns to scale or mean reversion in fund returns.